No longer Demospongiae: Homoscleromorpha formal nomination as a fourth class of Porifera. In: Maldonado M, Turon X, Becerro MA, Uriz MJ (eds) Ancient Animals, New Challenges. Sponge Research Developments. - Gazave, E.; Lapébie, P.; Ereskovsky, A.V.; Vacelet, J.; Renard, E.; Cárdenas, P.; Borchiellini, C. (Hydrobiologia, 2012)
Over the past few years, there has been growing interest among the sponge community in the phylogenetic position of the Homoscleromorpha (i.e. within or outside the class Demospongiae). Recent molecular analyses clearly show that the Homoscleromorpha forms a distinct clade separated from the Demospongiae and is composed of two families, Oscarellidae and Plakinidae. Within the currently more widely accepted hypothesis of a monophyletic Porifera, we formally propose here to raise Homoscleromorpha to the class rank (the fourth one). We, therefore, provide a definition and a formal diagnosis. In the supplementary materials, we also present an alternative classification of the Homoscleromorpha, following the PhyloCode.
Proceedings of the 8th International Sponge Conference